2008
DOI: 10.1002/dys.377
|View full text |Cite
|
Sign up to set email alerts
|

Free exploration of painting uncovers particularly loose yoking of saccades in dyslexics

Abstract: Binocular yoking of saccades is essential for single vision of words during reading. This study examines the quality of binocular coordination in individuals with dyslexia, independent of the process of reading. Fifteen dyslexia children (11.271.4 years) and 15 non-dyslexia individuals (8 children, aged 11.171.3 years, and 7 adults, 2473 years) were studied. Eye movements were recorded in two conditions. In the control condition, participants made saccades to a single target where the saccade direction and mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
5
16
0
Order By: Relevance
“…The invariance of the quality of binocular coordination with the condition is consistent with our previous study in normal young children (7 years old) and adults who showed similar binocular coordination in reading single words and in saccades to LEDs [13]. The present study suggests that binocular saccade disconjugacy is higher in dyslexics; this observation is further consolidated by another study from our group (Kapoula et al, submitted) [24] also examining saccades during free exploration of images. In the latter study, both age-matched and reading-matched comparisons are made.…”
Section: Discussionsupporting
confidence: 94%
“…The invariance of the quality of binocular coordination with the condition is consistent with our previous study in normal young children (7 years old) and adults who showed similar binocular coordination in reading single words and in saccades to LEDs [13]. The present study suggests that binocular saccade disconjugacy is higher in dyslexics; this observation is further consolidated by another study from our group (Kapoula et al, submitted) [24] also examining saccades during free exploration of images. In the latter study, both age-matched and reading-matched comparisons are made.…”
Section: Discussionsupporting
confidence: 94%
“…This saccade disconjugacy was also found to be present during reading [15]. In dyslexic children, the saccade disconjugacy was found to be increased when compared with age-matched non-dyslexics in a single word reading task [6] and this observation held for free explorations of paintings [16]. Moreover, the saccade disconjugacy is typically followed by a disconjugate drift during the subsequent fixation, which passively restores the disconjugacy due to saccade, i.e., a pulse-slide-step activity recorded in abducens neurons [17].…”
Section: Introductionmentioning
confidence: 66%
“…However, such a pattern was not present in dyslexic children when performing a word reading task [6] or free image exploration [16]. It remains to be seen whether this holds for text reading as well.…”
Section: Introductionmentioning
confidence: 91%
“…Binocular vision disruption at earlier age affects the normal development of the child. It also hinders the learning process 20. Therefore, strabismus should be corrected by pediatric ophthalmologists and appropriate orthoptic management should be attempted.…”
Section: Discussionmentioning
confidence: 99%